2015
DOI: 10.1016/j.bone.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Fractures on bisphosphonates in osteoporosis pseudoglioma syndrome (OPPG): pQCT shows poor bone density and structure

Abstract: Osteoporosis pseudoglioma syndrome (OPPG) is a rare autosomal recessive disorder of childhood osteoporosis and blindness due to inactivating mutations in LDL receptor-like protein 5 (LRP5). We and others have reported improvement in areal bone mineral density (aBMD) by DXA in OPPG on short term bisphosphonates. Long-term data on bisphosphonate use in OPPG and measures of volumetric BMD (vBMD) and cortical structure are not available. In addition, no long-term DXA data on untreated OPPG is available. The aims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
1
3
0
1
Order By: Relevance
“…Streeten et al reported significant increase in the areal BMD in OPPGS patients after treatment with bisphospho-nate, but trabecular volumetric BMD remained low. As a result, during long-term follow-up, there was no significant improvement in bone fractures (12), which was similar to the findings of our study. However, bisphosphonates cannot be considered as an ideal treatment for treatment of OPPG in some patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Streeten et al reported significant increase in the areal BMD in OPPGS patients after treatment with bisphospho-nate, but trabecular volumetric BMD remained low. As a result, during long-term follow-up, there was no significant improvement in bone fractures (12), which was similar to the findings of our study. However, bisphosphonates cannot be considered as an ideal treatment for treatment of OPPG in some patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, bisphosphonates cannot be considered as an ideal treatment for treatment of OPPG in some patients. Streeten et al reported fractures in three of nine OPPG patients with low-normal hip areal BMD after treatment with bisphosphonates (12). Our patient had multiple bone fractures after about seven years of pamidronate treatment.…”
Section: Discussionmentioning
confidence: 53%
“…human subjects, DXA-or pQCT-measured areal BMD, and volumetric BMD of cortical and trabecular bone, are typically expressed as Z-scores, where Z-scores lower than À2 are indicative for osteoporosis. (72)(73)(74) Previous studies using DXA and pQCT scanning in OPPG patients, carrying recessive LRP5 mutations, revealed decreased bone density (vBMD Z-score À1.57) and cortical bone area of the tibia (Z-score À2.19) (75) and decreased BMD of the lumbar spine (Z-scores between À1.2 and À7.8). (76) In addition, dominantly inherited LRP5 mutations were described to result in low bone mass phenotypes in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…OI or ALL). For example, in children with OPPG (characterised by impaired bone formation resulting in low bone turnover), although bisphosphonates produced an increase in aBMD, several of these children later suffered fractures even with improvement in DXA Z-scores ( 69 ).…”
Section: Anti-resorptive Agentsmentioning
confidence: 99%